2018
DOI: 10.1371/journal.pntd.0007035
|View full text |Cite
|
Sign up to set email alerts
|

The effects of prednisolone treatment on serological responses and lipid profiles in Ethiopian leprosy patients with Erythema Nodosum Leprosum reactions

Abstract: BackgroundErythema nodosum leprosum (ENL) is a systemic inflammatory complication occurring mainly in patients with lepromatous leprosy (LL) and borderline lepromatous leprosy (BL). Prednisolone is widely used for treatment of ENL reactions. However, it has been reported that prolonged treatment with prednisolone increases the risk for prednisolone-induced complications such as osteoporosis, diabetes, cataract and arteriosclerosis. It has been speculated that perhaps these complications result from lipid profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…A worrying fact, since the Brazilian Longitudinal Multicentric Study of Adult Health (ELSA Brazil) [55] classified as desirable levels of HDL-cholesterol �40 mg/dL for men and �50 mg/dL for women. These data are in agreement with recent findings from Silva et al (2018) and Negera et al (2018), which also observed lower levels of HDL-cholesterol in Mb patients compared to Pb and HC [56,57]. Other studies on serum lipids in leprosy also described lower levels of HDL-cholesterol in Mb patients [58,59].…”
Section: Discussionsupporting
confidence: 92%
“…A worrying fact, since the Brazilian Longitudinal Multicentric Study of Adult Health (ELSA Brazil) [55] classified as desirable levels of HDL-cholesterol �40 mg/dL for men and �50 mg/dL for women. These data are in agreement with recent findings from Silva et al (2018) and Negera et al (2018), which also observed lower levels of HDL-cholesterol in Mb patients compared to Pb and HC [56,57]. Other studies on serum lipids in leprosy also described lower levels of HDL-cholesterol in Mb patients [58,59].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, senescence in immune cells can induce immunosenescence, compromising the immune surveillance of NSCLC patients and increasing the risk of cancer-related adverse events such as cancer recurrence or cancer-specific death [ 34 , 35 , 36 ]. In addition, chronic inflammation, which is tightly connected to the pathogenesis of many chronic diseases [ 37 , 38 , 39 , 40 , 41 ], can negatively impact postsurgical outcomes and cancer prognosis; this can also partially explain why NSCLC patients with a higher burden of comorbidities have shorter survival. Further, NSCLC patients—particularly those with pre-existing chronic conditions—are often at risk of cardiac and/or respiratory complications, including but not limited to pneumonia, atrial fibrillation, and venous thromboembolism [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Same with research conducted by Zenha and his collage which states that there is a decrease in bacterial index in leprosy patients who have received MDT therapy for 12-24 months. 14 The study conducted by Negera (2018) 15 stated that the use of prednisolone in people with leprosy who experienced a reaction could reduce the antibody to M. leprae. In this case, pprednisolones treatment after 1 month decreased productivity from IL-10.…”
Section: Discussionmentioning
confidence: 99%